PENGARUH PEMANFAATAN MEDIA E-LEARNING “PORTAL RUMAH BELAJAR KEMENDIKBUD” TERHADAP HASIL BELAJAR - Br. Tarigan, Ima Pinensi; Widiastuti, Sussi; Gupita, Ixora (Jurnal Teknologi Pendidikan, 2025)
This research was conducted to determine the effect of using the E-Learning media " portal rumah belajar kemendikbud " on the learning outcomes of class X students at SMK Negeri 4 Palangka Raya in the 2023/2024 academic year. This type of research is descriptive research with a quantitative approach, with the subjects in this study being Class X Multimedia 1 students with a total of 32 people and Class X Multimedia 3 students with a total of 26 people. This study uses data collection tools in the form of questionnaires and documentation. The data analysis technique used is a simple linear regression test. The results showed that there was an effect of using the E-Learning media " portal rumah belajar kemendikbud “on the learning outcomes of 4 Palangka Raya State Vocational School Students in the 2024/2024 school year. This can be shown by the tcount value of 2.910, the regression coefficient (b) of 0.063 and a significance value of 0.005 because the regression coefficient has a positive value and a significant value (p) <0.05, it can be concluded that the better the utilization of E-Learning " portal rumah belajar kemendikbud, the better the learning outcomes of students at SMK Negeri 4 Palangka Raya for the 2023/2024 academic year.